2014
DOI: 10.1172/jci67280
|View full text |Cite
|
Sign up to set email alerts
|

Mutant p53–associated myosin-X upregulation promotes breast cancer invasion and metastasis

Abstract: Mutations of the tumor suppressor TP53 are present in many forms of human cancer and are associated with increased tumor cell invasion and metastasis. Several mechanisms have been identified for promoting dissemination of cancer cells with TP53 mutations, including increased targeting of integrins to the plasma membrane. Here, we demonstrate a role for the filopodia-inducing motor protein Myosin-X (Myo10) in mutant p53-driven cancer invasion. Analysis of gene expression profiles from 2 breast cancer data sets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
152
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(166 citation statements)
references
References 66 publications
13
152
1
Order By: Relevance
“…Two recent reports suggest that MyoX is an important marker of cancer invadopodia and cancer cell invasiveness. MyoX-dependent transport of integrins to the filopodium tip is essential for tumor cell invasion (Arjonen et al, 2014) and metastasis . These reports also demonstrate that MyoX expression is an important marker of aggressive and highly malignant breast cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent reports suggest that MyoX is an important marker of cancer invadopodia and cancer cell invasiveness. MyoX-dependent transport of integrins to the filopodium tip is essential for tumor cell invasion (Arjonen et al, 2014) and metastasis . These reports also demonstrate that MyoX expression is an important marker of aggressive and highly malignant breast cancers.…”
Section: Discussionmentioning
confidence: 99%
“…These data indicated that NOP14 enhanced the stability of mutp53 mRNA in PDAC cells. Interestingly, several of the abovementioned genes have been reported to be direct or indirect effectors of p53 in diverse cancers (2,3,(12)(13)(14). To determine whether these genes are regulated by mutp53 in PDAC cells, qRT-PCR, and immunoblotting analyses were performed and we found that mutp53 inhibition led to increased expression of P21 and decreased expression of PDGFRb, TGFB1, ZEB1, EGFR, and SMAD2 in PANC-1 and MIA PaCa-2 cells ( Fig.…”
Section: Nop14 Regulates Pdac Metastasis By Stabilizing Mutp53 Mrnamentioning
confidence: 83%
“…Among these changes is gaining the ability to alter cellular metabolic/catabolic machinery to create the most permissive conditions for invasion, dissemination, and survival (41). Many determinants of migration/invasion are cytoskeletal and vesicular trafficking components and biosynthetic/processing enzymes (42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…Altered expression of motor myosins has been linked to cancer cell survival, invasion, and metastasis, indicating that cytoskeletal components mediating cell contractility and organelle trafficking function in cancer cell behavior (44,49). Recent examples are Myosin-X upregulation in mutant p53-driven breast cancer models and Myosin-Va in colorectal cancer (42,50). In addition, up-regulation of other proteins involved in regulated exocytosis (that is, BAIAP3 and Rab27b) has been linked to tumorigenesis in desmoplastic small round cell tumor and breast cancer (51,52).…”
Section: /Arfmentioning
confidence: 99%